Pengaruh Green Financing dan Pengungkapan ESG terhadap Nilai Perusahaan Perbankan di BEI 2021–2024 - Sagita, Detriana; Pebriyani, Dewi (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of green financing and Environmental, Social, and Governance (ESG) disclosure on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. This research employs a quantitative approach using panel data regression analysis, with the Random Effect Model (REM) selected as the best estimation model. The dependent variable in this study is firm value, proxied by Tobin’s Q, while the independent variables include green financing, measured by the proportion of green loans to total credit, and ESG disclosure, measured using the GRI 2, GRI 300, and GRI 400 standards. The results indicate that both green financing and ESG disclosure have a positive but insignificant effect on firm value, either partially or simultaneously. The coefficient of determination (R² = 0.006229) shows that only 0.62% of the variation in firm value can be explained by the two independent variables, while the remaining 99.38% is influenced by other factors outside the model. These findings suggest that the implementation of green financing and sustainability disclosure in the Indonesian banking sector has not yet produced a significant impact on enhancing firm value, emphasizing the need for stronger implementation and greater transparency to create sustainable economic value.